2007
DOI: 10.1038/sj.bjp.0707198
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of angiogenesis by dithiolethione‐modified NSAIDs and valproic acid

Abstract: Background and purpose: Angiogenesis involves multiple signaling pathways that must be considered when developing agents to modulate pathological angiogenesis. Because both cyclooxygenase inhibitors and dithioles have demonstrated antiangiogenic properties, we investigated the activities of a new class of anti-inflammatory drugs containing dithiolethione moieties (S-NSAIDs) and S-valproate. Experimental approach: Anti-angiogenic activities of S-NSAIDS, S-valproate, and the respective parent compounds were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 74 publications
4
64
0
Order By: Relevance
“…Lethality was 100% at 5 μM thiolutin. Similar concentrations of two other dithioles, D3T and ADT, had little toxicity (Isenberg et al 2007). At 1 μM concentration, thiolutin-treated embryos (Fig.…”
Section: Thiolutin Disrupts Zebrafish Embryonic Development and Distumentioning
confidence: 99%
See 2 more Smart Citations
“…Lethality was 100% at 5 μM thiolutin. Similar concentrations of two other dithioles, D3T and ADT, had little toxicity (Isenberg et al 2007). At 1 μM concentration, thiolutin-treated embryos (Fig.…”
Section: Thiolutin Disrupts Zebrafish Embryonic Development and Distumentioning
confidence: 99%
“…1b)-treated embryos, with minimal disruption of the trunk vasculature. ADT-treated embryos showed vascular and morphological defects only at a fivefold-higher concentration (Isenberg et al 2007, and data not shown). Vascular defects in thiolutin embryos could not be independently assessed above 1 μM due to lethality, but thiolutin concentrations of 1 μM or less showed dose-dependent circulatory defects at 26 hpf when compared to age-matched DMSO-treated embryos (Fig.…”
Section: Thiolutin Disrupts Zebrafish Embryonic Development and Distumentioning
confidence: 99%
See 1 more Smart Citation
“…Dithiolethiones and related compounds have previously been explored as inhibitors of carcinogenesis and have shown considerable promise in animal models of edema and gastrointestinal inflammation (extensively reviewed in [114,115]; summarized in Table 2). However, it is possible that some of the observed biological effects associated with ADT-OH derivatives were due to the dithiolethione moiety itself, rather than released H 2 S. Indeed, an examination of the pertinent literature shows that dithiolethiones, including ADT-OH, are reactive with thiols and elicit several effects that may not be due to H 2 S. For example, Isenberg et al [116] and Moody et al [117] recently showed that the dithiolethione moiety of ADT-OH-modified NSAIDs and valproate rather than released H 2 S inhibited angiogenesis and cell proliferation. Others have shown dithiolethiones to induce the synthesis of phase II enzymes (e.g., glutathione-S-transferase, NAD[P]H, quinone oxidoreductase), GSH reductase and catalase [118][119][120][121][122].…”
Section: Perspectivementioning
confidence: 99%
“…Many of these have been designed with the specific intent of delivering controlled levels of H 2 S gas to tissues. Of particular interest are a number of structurally divergent molecule classes encompassing H 2 S releasing nonsteroidal antiinflammatory drugs (Isenberg et al, 2007;Sparatore et al, 2009), L-cysteine activated arylthioamide H 2 S donor molecules (Martelli et al, 2013), caged gem-dithiol derivatives that release H 2 S upon light stimulation (DevarieBaez et al, 2013) and molecules that release H 2 S in aqueous systems. Many of these compounds, that are now available commercially, have been reviewed elsewhere (Kashfi & Olson, 2013;Song et al, 2014).…”
Section: Why Slow Releasing H 2 S Donors?mentioning
confidence: 99%